Evaluation of Clients’ Satisfaction towards Primary Health Care Centers Services at Baghdad City - taha, tareq; jabbar, wissam (Iraqi National Journal of Nursing Specialties, 2017)
Objective: To evaluate the client’s satisfaction about the services provided in primary health care centers in the city of Baghdad and its impact on the improvement of services. Methodology: A simple random sample consisting of (200) clients to primary health care centers in the city of Baghdad, (15-20) clients for each center using a questionnaire to evaluate the client’s satisfaction for the service and the use of the direct method of interview, which lasts for (6-10) minutes. Results: Results of the study show that the number of men visits to primary health care centers, fewer women This indicates that the most important responsibilities of family members and private health care is the responsibility of women than men, especially in the eastern communities, and have shown that pregnant women aged between 30-39 years are more visit to primary health care centers due to pregnancy and its complications and most satisfaction towards primary health care services. The study reported that the visit rate was higher for the unemployed, because of the free health services, and were more satisfied with the services provided, and the study showed that the Ministry of Health paid great attention by taking care of the buildings and halls in primary health care centers in the city of Baghdad. The efficiency of the prescribed form to evaluate the satisfaction of visitors to primary health care centers and found that the form questioner meet 75% of the study. Recommendation:The study recommends an increase community awareness of the importance of primary health care services and that the services provided are not only for women but for men and women alike. Community education towards primary health care, health services and private school administrations to guide students and their parents to visit care centers to take advantage of the services provided and the Ministry of Health should be based to improving the quality of services provided to women, particularly maternal and child care